Taste of K-pop: Korean Music Selling System - SUGUMAR, PIRAVINRAJ; Mohamad Firdaus Ab Aziz (Applied Information Technology And Computer Science, 2026)
The rising popularity of K-pop in Malaysia has increased demand for merchandise like albums, lightsticks, and photocards. However, general e-commerce platforms such as Shopee and Lazada do not cater specifically to K-pop items, making it difficult for fans to find and trade merchandise efficiently. These platforms also lack trust, authenticity, and community spaces for fans to connect. To address these challenges, the "Taste of KPOP" project was created as a dedicated e-commerce platform for Malaysian K-pop fans. The platform aims to simplify buying and selling merchandise through features like user registration, secure payments, specialized product listings, and a review system to build trust. Using an agile development model, the project focuses on flexibility and continuous feedback. This allows for flexibility by working in short cycles called sprints. After each sprint, feedback is collected, and changes can be made quickly. The platform also offers a community space for fans to interact. Future updates will expand the platform’s reach and enhance the user experience based on feedback.